An engineering perspective on the quality of the automotive push-buttons' haptic feedback in optimal and suboptimal interactions. (2nd September 2019) - Valverde, Nuno; Ribeiro, A.M.R.; Henriques, Elsa; Fontul, Mihail
Abstract : Designing automotive Human–Machine Interfaces falls into a resource-intensive and iterative prototyping process. Design inputs, including those resulting from an automaker's brand sense, frequently emerge from subjectively evaluating the products. This research aims at characterising the haptic feedback afforded by push-buttons' prototypes. It introduces quality criteria, by assessing feedback degradation when actuations depart from optimal conditions and fall into suboptimal interactions. From reviewing published literature in HMIs', metrics for characterising haptic profiles are insufficient and the taxonomy is unclear, redundant and conflicting. Experiments were built, providing prototypes with distinguishable feedbacks. Their haptic profile was measured and translated into unique engineering parameters, including new metrics to address feedback resilience in suboptimal actuations. Perceptual processes are involved, with the interpretation of data extended by using human Just-Noticeable-Differences (JNDs) thresholds and a psychophysical model of finger compliance. The outcome of this research is twofold: a contribution to a better understanding of push-buttons haptic feedback, enabling the definition of desired interactions and meeting brand sense expectations in early design stages of HMIs; and a proposed taxonomy for characterising push-button haptic feedback. The results achieved and the research methodology are extendable for similar design activities that require Human–Machine interactions, development of HMIs in general, and virtualisation of haptics.